THU0120 Long Term Safety and Efficacy of Biosimilar Infliximab among Patients with Inflammatory Arthritis Switched from Reference Product. (15th July 2016) - Abdalla, A.; Byrne, N.E.; Conway, R.; Walsh, T.; Mannion, G.; Hanly, M.; O'Sullivan, M.; Curran, A.; Carey, J.J.
Abstract : Background: Biologic medications are effective treatments for inflammatory arthritis, however they are expensive, costing around €15, 000 per patient per year, or 5% of the annual healthcare budget in Ireland. Measures to reduce this cost without sacrificing efficacy or safety are important. Studies switching patients to cheaper approved biosimilar products are few. Objectives: To evaluate the efficacy and safety of biosimilar Infliximab in adult patients with inflammatory arthritis switched from reference product in our centre. Methods: In April 2014 all patients attending our rheumatology service for Infliximab infusions were switched from reference product to a biosimilar infliximab following verbal consent and hospital approval. Our local I.R.B. approved a retrospective review of these patients following requests from other centres for information on our experience. Results: 34 patients with inflammatory arthritis were switched from reference product Infliximab in 2014: 50% female, mean (SD) age 55 years (12.9), mean disease duration 14.8 years (9.7), mean duration on infliximab 70 months (59.6) and two thirds were taking oral DMARDs. There was no difference in efficacy or safety in the first 6 months of therapy. By the end of 2015, the mean follow-up on biosimilar infliximab was 15.8 months (6.3). Our results show no significant difference in HAQ score, patient global assessment of disease activity, number of disease flares or medication dose between the originator and the biosimilar Infliximab. However reported pain and CRP values were significantly higher during the longer follow-up period ( p value 0.028, 0.001 respectively). There was no significant difference in the number of adverse events or infusion reactions during similar follow-up periods, or the number of patients who discontinued therapy (3 Vs 5). 1 frail patient with multiple co-morbidities died during follow-up. Substantial savings were obtained by using the biosimilar product. Conclusions: Our patients experienced similar efficacy and safety for managing their arthritis with biosimilar infliximab as reference product Infliximab, but at a much lower cost. Acknowledgement: National University of Ireland, Galway for statistical software support. Disclosure of Interest: A. Abdalla: None declared, N. Byrne: None declared, R. Conway: None declared, T. Walsh: None declared, G. Mannion: None declared, M. Hanly: None declared, M. O'Sullivan: None declared, A. Curran: None declared, J. Carey Consultant for: Consulting fees and speaker fees by MSD Ireland and Hospira and received travel support and grants from MSD Ireland and Centrecor, USA